Effect of Ca Concentration on Microstructure and Mechanical Properties of As-Cast and As-Extruded Quasicrystal-Strengthened Mg-7.2Zn-2.4Gd Alloy - Jianchun Sun; Yilong Ma; Hongwei Miao; Kejian Li; Chunhong Li; Hua Huang (Advances in Materials Science and Engineering)
Quasicrystal-strengthened Mg-Zn-RE (RE = rare-earth element) alloys have been investigated extensively due to their excellent mechanical properties. Here, we prepare quasicrystal-strengthened Mg-7.2Zn-2.4Gd (wt.%) alloy with different concentrations of Ca addition (0, 0.16, 0.32, and 0.64 wt.%) by traditional gravity casting, followed by extrusion at 573 K with the extrusion ratio of 9 : 1. The microstructure and room temperature tensile properties of as-cast and as-extruded alloys are characterized. With the addition of the trace amount of Ca, the I-phase tends to transfer into W-phase due to the appearance of Mg2Ca and Mg6Zn3Ca2. As a consequence, the mechanical properties of the as-cast Ca containing alloys are downgraded. After extrusion, in comparison to the as-cast alloys, microstructure of the four types of alloys is refined and mechanical property is enhanced greatly. With the increasing of Ca concentration, the grain size is decreased gradually. However, the yield strength of the alloys is decreased to about 230 MPa and then up to 269 MPa, while the elongation increases first from 12.9% to 13.6% yet then decreases to 9.9%.